Pengaruh Gender, Locus of Control, dan Equity Sensitivity terhadap Perilaku Etis Mahasiswa Akuntansi Universitas Andalas - Medelyn Sonya Mikoshi; Yurniwati Yurniwati; Denny Yohana (Universitas Batanghari Jambi, 2020)
This study aims to identify and obtain empirical evidence of the influence of Gender, Locus of Control and Equity Sensitivity on the Ethical Behavior of Accounting Students. This research was conducted on accounting students who are currently taking Audit courses at Andalas University with a sample of 380 accounting students. This study uses dependent variables of ethical behavior and independent variables, namely Gender, Locus of Control and Equity Sensitivity.This study uses the SmartPLS Ver 2 M3 software to analyze the relationship between the influence of Gender, Locus of Control and Equity Sensitivity on the ethical behavior of accounting students. From the results of data research and discussion conducted using SEM-PLS, it is obtained that Gender has no effect on students' ethical attitudes, Locus of Control does not affect Ethical Behavior while Equity Sensitivity influences Ethical Behavior.